Regularização fundiária e proteção dos direitos de quilombos: Análise da legislação e prática de territorialização de comunidades tradicionais no Maranhão - FORMIGA, Daniel Henrique Dias (2023)
Guaranteed access by quilombola communities to the land they traditionally need to reproduce their ways of life is one of the most relevant factors for maintaining their identities, although this right was only incorporated into the Brazilian legal system with the advent of the Federal Constitution. of 1988, nationwide, and with the Maranhão Constitution of 1989, locally. In this context, the present research aims to analyze the adequacy of the legal and administrative instruments used by the Public Administration of Maranhão, through ITERMA, for the concretion of the territorial rights of the traditional quilombola peoples in the state. The work takes the following line: it begins with the definition of the object of protection, highlighting the importance of territories in the formation of the identity of quilombos, as well as the devices of Brazilian and international law that deal with the matter, especially with the elucidation of the different approaches in each of the spheres; it then proceeds with a description of the procedures for the territorialization of quilombo lands, drawing parallels between the experience at the federal level and the model constructed for the Maranhão scenario; finally, the adequacy of the territorialization instruments used by the State of Maranhão is examined in relation to the legal guidelines and the central elements of the culture of the quilombola peoples, both in the abstract and in the concrete application to the case of the Quilombola Territory Sesmaria dos Jardins. The research used the dialectical method, through a bibliographical review of published works on the themes addressed and the case study of an administrative process conducted under the current state norms of Maranhão, with the objective of understanding the relationships, connections and adaptations between the culture of the communities quilombolas and the norms created to materialize their rights.